P40 Spontaneous pneumomediastinum in mixed connective tissue disease. (20th April 2020) - Hasan, Fuad; Kumar, Vinod; Silburn, Suzy; Thomson, Rosanna
Abstract: Background: Spontaneous pneumomediastinum refers to dissection of free air from the airways on lung parenchyma into the mediastinal structures without any antecedent thoracic trauma or surgical intervention. Pneumomediastinum has been described as a rare complication of connective tissue disease, most commonly in dermatomyositis and polymyositis. Here we report 2 cases of mixed connective tissue disease (MCTD) who developed pneumomediastinum. Methods: The first case was a 76 year old male undergoing assessment for MCTD. During assessment, he was found to have bi-basal crepitations without any obvious respiratory symptom. He was on steroids for last 4 weeks for proteinuria. His High- resolution CT scan (HRCT) showed pneumomediastinum with evidence of Interstitial lung disease (ILD) without any complication. He was monitored closely and his pneumomediastinum resolved without any intervention. The second case was a 49 year old female with known MCTD & was on steroids for 5 months. She was admitted to the hospital with weight loss and dysphagia. This was a long hospital stay during which she developed pneumomediastinum with pneumothorax and surgical emphysema around the neck. She required ICU admission and was transferred to cardiothoracic centre where she underwent bronchoscopy, VATS inspection and required chest drains. Results: In both cases there were similarities where both patients with MCTD were on variable duration of steroids & had ILD. They then developed pneumomediastinum with surgical emphysema, however their course was quite contrasting where the first case was relatively benign & resolved without any intervention while the second one required long ITU stay with multiple complications and interventions. Conclusion: Spontaneous pneumomediastinum is an uncommon manifestation of CTD and only few cases have been reported with MCTD. Although spontaneous mediastinum seems to be associated with a relatively benign short-term course, one should be wary of complications and have low threshold for investigating for any new lung symptoms in context of CTD. It is uncertain whether severity of MCTD or duration of steroids use impacts the progress of spontaneous pneumomediastinum as there are very limited number of cases. Disclosures: F. Hasan None. V. Kumar None. S. Silburn None. R. Thomson None.